BREAKING THE BOUNDS: EXPLORING FLOUTED MAXIMS ON THE TALK SHOW ‘TALKPOD’ - A CASE STUDY OF CHATEEZ’S LANGUAGE PLAY : - - Husni, Nabillah; Hanieviya Ouelya, Dyiena; Farihatul Maula, Novi; Ramadhany, Arjuna (Universitas Hasanuddin, 2023)
Maxim are the communicative strategy as a guideline for effective and cooperative communication proposed by Grice. This research focused to presents the results of research by Chateez utterances and conducted using a qualitative approach, data source was collected through video recordings in programs talkshow-talkpod episodes. Based on data, were found all types of flouting maxim in the program, which consist flouting of maxim of quantity, flouting of maxim of quality, flouting of maxim of relevance, and flouting of maxim of manner. The most dominant flouting that occurs in this research is flouting of maxim of quantity and rarely occurs is flouting of maxim of relevance. The purpose of this research, to analyze several causes of flouting maxim and classified the types of flouting of maxim. This research can provide a deeper understanding of how flouting maxim occurs in conversation through the application of maxim principles in communication.